Towards a lower tax burden in Poland - Karwowski, Jacek (Ograniczenie obciążeń podatkowych w Polsce, 2011)
The purpose of this paper is to analyze the possibilities and implications of reducing the income tax burden for the Polish economy. Two major proposals are presented: 1) halving the tax-GDP ratio to below 20% and changing the structure of budget expenses to reflect the real needs of the society (e.g. public order and safety, education, R&D, health, infrastructure); and 2) reducing, and finally abolishing income taxes to positively influence economic growth and welfare in Poland. Several implications on the conduct of these proposals are discussed. Paper findings are subject to a discussion concerning the flat tax debate
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 67-78
Keywords: tax burden; budget deficit; flat tax; income tax; government spending